Investigating POU3F4 in cancer: Expression patterns, prognostic implications, and functional roles in tumor immunity - Weiwei Chen; Yaya Ji; Rui Wang; Ruijie Ji; Yujian Lin; Yuhang Wu; Lehan Liu; Tianle Sha; Wen Li; Lei Zhang; Longfei Yang; Xinhua Zhang; et al. (Heliyon)
Research has demonstrated that POU3F4 is integral to various cancers, in addition to its significance in inner ear development, pancreatic differentiation, as well as neural stem cell differentiation. Nevertheless, comprehensive pan-cancer analyses focusing on POU3F4 remain limited. This study aims to assess the prognostic value of POU3F4 in thirty-three cancers and explore its immune-related functions. Based on data from The Cancer Genome Atlas (TCGA), Cancer Cell Line Encyclopedia (CCLE), Genotype-Tissue Expression (GTE), and Gene Set Cancer Analysis (GSCA), we employed various bioinformatics approaches to investigate the potential carcinogenic effects of POU3F4. Our study encompassed DNA methylation, RNA methylation, tumor mutation burden (TMB), mismatch repair (MMR) genes, microsatellite instability (MSI), the relationship between POU3F4 and prognosis, and immune cell infiltration (ICI) across different tumors. The analysis revealed that POU3F4 expression is typically low in most cancers but is elevated in breast invasive carcinoma, glioblastoma multiforme (GBM), liver hepatocellular carcinoma, and thyroid carcinoma, with the highest levels in GBM. Additionally, POU3F4 expression correlates with cancer prognosis, either positively or negatively. The expression of POU3F4 demonstrated significant associations with MSI in four cancers and TMB in six cancers. POU3F4 expression was significantly linked to DNA methylation in 13 cancer types and RNA methylation in most cancers. It also correlated with the tumor immune microenvironment, immune-related genes, immune checkpoint inhibitors, and drug resistance in various cancers. In vitro experiments demonstrated that POU3F4 enhances cell viability, proliferation, and migration in GBM. Our findings indicate that, given its critical role in carcinogenesis and tumor immunity, POU3F4 serves as a prognostic marker in diverse malignancies.